Redox-neutral photocatalytic hydrodealkenylation of aryl olefins - Ke Liao; Chunming Gui; Ziming Cao; Yong Huang; Jiean Chen (Nature Communications)
Abstract Carbon-carbon bond cleavage is a transformative strategy in chemical synthesis, particularly for modifying complex molecules. While the cleavage of C(sp²)=C(sp²) π-bonds is relatively straightforward, the selective cleavage of unpolarized C(sp²)–C(sp³) σ-bonds remains a significant challenge. In this study, we present a redox-neutral approach for hydrodealkenylation, enabling the selective cleavage of C(sp²)–C(sp³) σ-bonds in aryl olefins. This reaction proceeds via a cascade of aryl radical cation-mediated open-shell steps under photoredox conditions, incorporating an alkene migration step that exhibits high selectivity and synthetic versatility. This protocol facilitates the selective removal of a vinyl group from arylalkene substrates, yielding isolable fragments. Moreover, this method extends beyond single-bond cleavage by enabling a domino reaction sequence capable of cleaving multiple inert carbon-carbon σ-bonds and allowing programmable chain homologation. This work advances the field of σ-bond cleavage and functionalization, offering a versatile tool for the molecular editing of hydrocarbons with significant implications for synthetic chemistry and the development of novel chemical transformations.